Instilling Entrepreneurial Values through Market Day Activities in Indonesian Islamic Schools - Akbari; Alrefi (Edukasi, 2024)
In Indonesia, only 0.18% of the total population, around 225 million, choose to become entrepreneurs, while in Singapore, the percentage is 4%. Unemployment in Indonesia remains an unresolved problem. This problem proves the importance of teaching children about entrepreneurship from an early age. One effective strategy is through organizing market day activities at Faza Islamic School of Early Childhood Education in Palembang. The participants were 30 students in even semester of Faza Islamic School Palembang in Early Childhood Education. The purpose of this research was to find out the process of instilling entrepreneurial values in children through market day activities. The method employed in this study was qualitative, using an interactive engineering model. The technique for collecting data in this research were using observation, interviews and documentation techniques. The data analysis technique in this research used the Miles and Huberman model,  a qualitative data analysis path, namely, collecting data related to research, reducing data that is deemed appropriate, presenting data related to research themes and topics and drawing data conclusions. The results of this research showed that market day activities could increase entrepreneurial values, including independence, creative risk taking, leadership and action orientation. In conclusion, market day activities were able to foster attitudes and improve children's entrepreneurial values in Faza Islamic School, Palembang City.